ANALISIS IMPLEMENTASI PEMBELAJARAN PENDIDIKAN PANCASILA BERBASIS BHINNEKA TUNGGAL IKA DALAM MENGEMBANGKAN TOLERANSI SISWA KELAS VIII FASE D DI SMP NEGERI 17 KOTA JAMBI - Syafira, Nabilla; Aditya Candra, Alif; Ichsan, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Indonesia's diversity in terms of religion, ethnicity, culture, language, and social background requires the strengthening of tolerance values through education. Pancasila Education plays a strategic role in instilling the values of Bhinneka Tunggal Ika so that students are able to appreciate differences and live harmoniously in a multicultural environment. This study aims to analyze the implementation of Pancasila Education based on Bhinneka Tunggal Ika in developing students' tolerance and to identify the supporting and inhibiting factors in its implementation at SMP Negeri 17 Kota Jambi. This study employed a qualitative approach using a case study design. The research involved Pancasila Education teachers, the Vice Principal for Curriculum Affairs, and Class VIII Phase D students. Data were collected through observation, interviews, and documentation, while data validity was ensured through source, technique, and time triangulation. Data were analyzed using the Miles and Huberman interactive model. The findings indicate that the implementation of Pancasila Education based on Bhinneka Tunggal Ika was carried out through diversity-related learning materials, heterogeneous group discussions, collaborative learning activities, teacher role modeling, and the habituation of respectful attitudes. The implementation contributed to the development of students' tolerance, reflected in their ability to respect differences, build cooperation, demonstrate empathy, and maintain peaceful relationships within the school environment. However, several challenges remain, including the influence of social media, peer environment, limited instructional time, and the inconsistency of some students in applying tolerance values.